Analysis of Protecting Lung Cancer Images Using Visual Cryptography - Sreeprada, V.; Vedavathi , K. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Linking the intelligent sensors and smart devices in the hospital ecosystem, medical data must be kept securely. To safeguard the privacy of patients, an intelligent working system requires improved security measures. Recently, sure imagine encryption methods based on compression sensing (CS) have been developed for securing images with visual security. In these schemes, both compression and encryption of the images are performed simultaneously, before being fixed into a holder image. The encrypted images are partial by the current systems’ presentation limits along with quality and efficiency of the reconstructed images. This paper develops an Improved Visually Secure Image Encryption (IVSIC) scheme which aims to handover real-time lung-cancer images securely, without degrading their quality. The greatest level of security of our proposed system is established by contrasts and imitations. In contrast to some newly developed schemes, it is also more effective and produces cipher and reconstructed images of higher quality.